Degradation of cross-linked fibrin by matrix metalloproteinase 3 (stromelysin 1): hydrolysis of the gamma Gly 404-Ala 405 peptide bond. - Bini, A; Itoh, Y; Kudryk, B; Nagase, H (1996)
Matrix metalloproteinases (MMPs) can degrade a number of proteins that constitute the extracellular matrix. Previous studies have shown that atherosclerotic plaques contain substantial amounts of fibrin(ogen)-related antigen, and more recently, MMPs have been identified in such lesions. The hypothesis that MMPs play a role in the degradation of fibrinogen (Fg) and cross-linked fibrin (XL-Fb) was investigated. Fibrinogen became thrombin-unclottable when treated with matrix metalloproteinase 3 (MMP-3, stromelysin 1) but not with matrix metalloproteinase 2 (MMP-2, gelatinase A). Incubation of XL-Fb clots (made with 125I-Fg) with MMP-3 resulted in complete lysis after 24 h. A D monomer-like fragment was generated by MMP-3 degradation of fibrinogen, XL-Fb, and fragment DD. Immunoreactivity with monoclonal antibody (MoAb)/4-2 (anti-gamma 392-406) but not with MoAb/4A5 (anti-gamma 397-411) suggested that a major cleavage site was within the sequence participating in the cross-linking of two gamma-chains. NH2-terminal sequence analysis of they gamma-chain of the D monomer-like fragment and of a dipeptide isolated from the MMP-3 digest of XL-fibrin identified the hydrolysis of the gamma Gly 404-Ala 405 peptide bond. These data indicate that the degradation of Fg and XL-Fb by MMP-3 is specific and different from plasmin. This mechanism of fibrinolysis might be of relevance in wound healing, inflammation, atherosclerosis, and other pathophysiological processes.